Cerebral watershed infarcts may be induced by hemodynamic changes in blood flow. (3rd June 2017) - Shi, Jingfei; Meng, Ran; Konakondla, Sanjay; Ding, Yuchuan; Duan, Yunxia; Wu, Di; Wang, Bincheng; Luo, Yinghao; Ji, Xunming
Abstract: Objectives: A watershed infarct is defined as an ischemic lesion at the border zones between territories of two major arteries. The pathogenesis of watershed infarcts, specifically whether they are caused by hemodynamic or embolic mechanisms, has long been debated. In this study, we aimed to examine whether watershed infarcts can be induced by altering the hemodynamic conditions in rats. Materials and Methods: In phase one, to determine the proper clamping duration for a reproducible infarct, 30 rats were equally divided into 5 subgroups and underwent bilateral common carotid artery (CCA) clamping for different durations (0.5, 1.0, 1.5, 2.0, and 3.0 hours). In phase two, to analyze the types of infarcts induced by bilateral CCA clamping, 40 rats were subjected to bilateral CCA clamping for 2 hours. As a control, 8 rats underwent all the operation procedures except bilateral CCA clamping. We performed 7.0T magnetic resonance imaging on the surviving rats on the second day to evaluate the extent of the infarcts. We further identified and examined the infarcts with brain slices stained using 2, 3, 5-triphenyltetrazolium chloride (TTC) on the third day. Results: After 2 hours of bilateral CCA clamping, cerebral infarction occurred in 42% of surviving rats (13/31). The majority of the ischemic lesions were located in watershed regions of the brain, demonstrated by both MRI and TTC staining. Conclusion: Watershed infarcts were induced through changing hemodynamic conditions by bilateral CCA clamping in rats. This method may lead to the development of a reliable rodent model for watershed infarcts.